EVALUASI SIMPANG BERSINYAL DI SIMPANG PANAM KOTA PEKANBARU DARI ASPEK LALU LINTAS - Andini Salsabila Fitra; Hendri Rahmat; Fadrizal Lubis (Racic : Rab Construction Research, 2025)
According to BPS Pekanbaru City Year 2023, the urbanization rate of 2,99% per year increases the volume of motor vehicles, especially at Panam Intersection which is the meeting point of Jl. Hr. Soebrantas, Jl. Raya Pekanbaru, Jl. Kubang Raya, and Jl. Garuda Sakti. The traffic light cycle time reaches 208 seconds, exceeding the PKJI 2023 threshold for 4 phases (80-130 seconds), triggering congestion of up to 200 meters on Jl. Hr. Soebrantas and Jl. Raya Pekanbaru. This study aims to evaluate the performance of the signalized intersection at Panam Intersection with alternative fly over construction. The research method uses PKJI 2023 with analysis of existing conditions and alternative scenarios. The results showed existing conditions with a degree of saturation (DJ) of 0,92> 0,85, an intersection delay of 67,26 seconds /mp, and a maximum queue length of 399 meters with category F level of service. After the construction of the flyover, the DJ decreased to 0,71, the delay to 13,54 seconds / smp, and the maximum queue length dropped to 99 meters with a category B level of service. A combination with road widening or signal phase changes is recommended to optimize traffic management.